THE EFFECT OF WASTE MANAGEMENT IN SPATIAL ORGANIZATION IN PALAKALI CREATIVE ART SPACE - Triwibowo, Adi Surja (Journal of Development and Integrated Engineering, 2023)
Garbage is produced from various types of human activities and is one of the environmental problems that have an impact not only on the environment but also on human health, such as environmental pollution, death of animals or plants, and the emergence of diseases caused by vectors. One of the efforts to reduce is by sorting waste based on its type so that it is easier to determine the next processing method and implementing 3R (reuse, reduce, and recycle) to prevent and reduce waste generation. Palakali Creative Art Space already has trash cans based on type (organic, non-organic and Hazardous Toxic/B3), but the practice of sorting waste according to these criteria has not been carried out.